VD_FINDINFO Jug / 2018 / 405 vom 13. November 2018 - VD Tribunal cantonal (2018)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, ACTION PÉNALE, PRESCRIPTION, INTERRUPTION DU DÉLAI, PARTIE CIVILE | 41 CO, 60 al. 2 CO, 43 al. 1 CP